Design and development of control and monitoring hydroponic system - Mujtahidin, Muhammad Hanafi; Mohd Shah, Ahmad Feirdaous; Amin Jais, Ahmadul Sayyidi; Mohd Annuar, Khalil Azha; Mohamad Sapiee, Mohd Razali (Institute of Advanced Engineering and Science, 2024)
The global agriculture system faces significant challenges in meeting the growing demand for food production, particularly given projections that the world's population will reach 70% by 2050. Hydroponic farming is an increasingly popular technique in this field, offering a promising solution to these challenges. This paper will present the improvement of the current traditional hydroponic method by providing a system that can be used to monitor and control the important element in order to help the plant grow up smoothly. This proposed system is quite efficient and user-friendly that can be used by anyone. This is a combination of a traditional hydroponic system, an automatic control system and a smartphone. The primary objective is to develop a smart system capable of monitoring and controlling potential hydrogen (pH) levels, a key factor that affects hydroponic plant growth. Ultimately, this paper offers an alternative approach to address the challenges of the existing agricultural system and promote the production of clean, disease-free, and healthy food for a better future.